* تركيبة السلطة المختصة بالتشريع في النظامين العراقي وااللماني ) دراسة مقارنة ( - Sarhang Hameed Baqzanji; Badrkhan Hasan Ahmed (QALAAI ZANIST JOURNAL, 2019)
The characteristic of legislative in federal system clearly reflects at the level of federal government, and its components. On the other hand, this process makes legislative into two different types, which based on bicameral model that consists of (Lower Council) that they represent people in general, and (Upper Council) that represents federal units/regions. Besides, at the level of federal units, legislative authority will once again to be elected in accordance of federal constitution, and region or federal unit’s constitution. This authority usually comprises of a single council bur rarely includes a couple of councils. So there will be one more legal power. Hence, Legislative authority in federal country includes some kind of complexity and pluralism due to distribution of powers among central authority and its regions/units. This constantly effects on legislation process even reflects on procedures, and guarantees to remain federal units in a way should secure the unitary and plurality of legislation in framework of this federalism state.